O-031 Combinational therapy following elvo in a mouse model of stroke demonstrates new frontiers in neuroprotection: the mavaric trial. (23rd July 2017) - Maniskas, M; Trout, A; Goodman, J; Bix, G; Fraser, J
Abstract : Stroke remains a leading cause of morbidity and mortality in the United States. Potential therapies have encountered significant barriers in attempts to translate bench to bedside research. Because of this, we have evaluated novel roles for FDA approved drugs, repurposed for treating stroke. Two such drugs, verapamil and magnesium, represent drug classes with a long history in neuroprotection trials with mixed results. Using an intra-arterial (IA) model developed in our lab, we selectively delivered our agents of interest to the stroke affected region following experimental stroke and successful recanalization. In addition, we studied the effect of the drugs on primary cortical neurons (PCN) exposed to oxygen glucose deprivation (OGD) in vitro . In vivo experiments used 16 week old C57/Bl6 male mice that underwent a tandem transient common carotid/middle cerebral artery occlusion for 60 min. Following successful recanalization, verapamil (1.76 mg/kg) and magnesium (176 mg/kg) were administered IA through the internal carotid artery using a previously determined flow rate and injection volume. Physiological measurements (heart rate and blood pressure) were monitored for potential deleterious effects during and ten minutes following IA drug administration. A neurological score was used to determine differences in functional outcome on post-stroke days (PSD) 1 and 7. On PSD 7, animals were euthanized and brains flash frozen for immunohistochemistry analysis of infarct volume, mature neurons, and apoptosis. For comparison, single doses of verapamil, magnesium and saline were also administered IA. In vitro PCNs from C57/Bl6 embryonic day 18 mice were exposed to OGD ("stroke in a dish") for 30 min in a sealed chamber. Following 30 min OGD, glucose deficient media was replaced with normal PCN media combined with verapamil (250, 325, and 500 ng) and magnesium (0.5, 1 and 2 mM) for 24 hours. Analysis was performed using Hoechst assay for cell viability, MAP2 for neurite extension and Bcl-2 for apoptosis. Control plates did not undergo OGD but did receive drug treatment. Both in vivo and in vitro results demonstrated that combinational therapy is safe and provides neuroprotection. In vivo results demonstrated drug administration did not have a negative effect on physiological measures during and after IA administration. Infarct volume shows a significant reduction in size when compared to control animals at PSD 7. Immunohistochemistry for mature neurons showed a greater population of healthy neurons in the treated group when compared to the control group. This correlated with measurements for apoptosis, as fewer number of apoptotic cells were found in the treated infarcted region when compared to control animals. In vitro results following OGD demonstrated direct neuroprotection of combinational drug therapy using Hoechst assay analysis compared to control. Further, neurite outgrowth measurements using MAP2 showed a greater number of primary, secondary and tertiary neurites compared to control. Lastly, Bcl-2 a measure of apoptosis showed combinational therapy had decreased apoptosis when compared to control. Combinational IA therapy with verapamil and magnesium is safe and effective for treatment of experimental ischemic stroke and may be an effective "stroke therapy cocktail" worthy of clinical study. Disclosures: M. Maniskas: None. A. Trout: None. J. Goodman: None. G. Bix: None. J. Fraser: None.